Optimizing the Role of BUMDes in Developing MSMEs in Lemujud Village Good Corporate Governance: Optimalisasi Peran BUMDes dalam Mengembangkan UMKM di Desa Lemujud Good Corporate Governance - Phahlevi , Rifqi Ridlo; Purwaningsih , Sri Budi; Choiriyah, Ilmi Usrotin; Faizin, Moh. (Procedia of Social Sciences and Humanities, 2022)
The development of BUMDes is one of the methods used by the government to develop and improve the economy of rural communities and increase the income of Village Original Income, including for Lemjut Village. Lemujut village has a BUMDes that is already operating with several existing business units including kiosk rental business units, PAMSIMAS, village banks and TPS management. The obstacle faced is the lack of human resources (HR) in managing the business units in the BUMDes of Lemujut. In addition, the understanding of the village government and the management of the Lemujut bumdesa which is less related to the mechanism of the bumdesa and the legal culture problems that occur are one of the obstacles in the development of the Lemujut bumdesa. The solution offered is for the village government to carry out a Good Governance corporate scheme in the management of the Lemujut bumdesa. The expected output target is the existence of a mechanism in a good BUMDes governance scheme, which provides good benefits for BUMDes Lemujut and MSMEs as a solution for the development of BUMDes. In addition, it also provides convenience for third parties who want to become investors in business units managed by BUMDes.